Accordance between different nutritional classification criteria in older adults, Colombia - Forero-Ballesteros, Luis Carlos; Forero-Torres, Ana Yibby (Universidad y Salud, 2022)
Introduction: Aging is an irreversible process that generates a permanent increase in the 60 and older population. This vulnerable population lives in conditions of disability, neglect, lack of attention, and they present with illnesses related to their nutritional status, which is why it is necessary to understand it fully. Objective: To analyze the accordance between different criteria of nutritional classification according to the Body Mass Index, using an aging population survey, Colombia 2015. Materials and methods: Four criteria were used as well as accordance between categories of nutritional status. Direct and weighted Kappa indices were calculated. Results: The accordance was moderate and good, the lowest proportion of low weight (3.4%) was obtained using the World Health Organization criteria and the highest (22.6%) with the Pan American Health Organization (p<0.05). Low weight is increased as one ages, while excessive weight decreases. Conclusions: Nutritional classification changes depending on the criteria and cut-off points. The criteria of the Spanish Society of Parenteral and Enteral Nutrition had the highest accordance with the World Health Organization and the best capacity in detecting nutritional deficiency in the older adult population.